Potential of CXCR4 antagonists for the treatment of metastatic lung cancer. Issue 4 (April 2011) - Burger, Jan A; Stewart, David J; Wald, Ori; Peled, Amnon
Despite advances in surgery, chemotherapy and radiotherapy over the last decades, the death rate from lung cancer has remained largely unchanged, which is mainly due to metastatic disease. Because of the overall poor prognosis, new treatment strategies for lung cancer patients are urgently needed, and targeting CXCR4 constitutes such a novel, attractive strategy. Tumor cell migration and metastasis share many similarities with leukocyte trafficking, which is critically regulated by chemokine receptors and adhesion molecules. Lung cancer cells express CXCR4 (CD184), a seven-transmembrane G-protein-coupled chemokine receptor. Stromal cells within the tumor microenvironment constitutively secrete stromal cell-derived factor-1 (SDF-1/CXCL12), the ligand for CXCR4. Activation of CXCR4 induces lung cancer cell migration and adhesion to stromal cells, which in turn provides growth- and drug-resistance signals to the tumor cells. CXCR4 antagonists, such as Plerixafor (AMD3100) and T140 analogues (TN14003/BKT140), can disrupt CXCR4-mediated tumor cell adhesion to stromal cells and sensitize lung cancer cells to cytotoxic drugs. Therefore, targeting the CXCR4––CXCL12 axis is a novel, attractive therapeutic approach in small-cell lung cancer and non-small-cell lung cancer. In this article, we summarize data about the cellular and molecular microenvironment in small-cell lung cancer and non-small-cell lung cancer, as well as the role of CXCR4 in tumor––stroma crosstalk. In addition, we review the current status of the preclinical and clinical development of CXCR4 antagonists.